ELECTRONIC AGREEMENTS FROM THE LENS OF THE LEGAL PERSPECTIVE “LAW AS A TOOL OF SOCIAL ENGINEERING” PROPOSED BY ROSCOE POUND - Imelda Martinelli; Christian Samuel Lodoe Haga; I Putu Juni Artana (Bengkoelen Justice : Jurnal Ilmu Hukum, 2023)
The purpose of this research is to provide a juridical analysis of electronic agreements from the legal perspective of “Law as A Tool Of Social Engineering” coined by Roscoe Pound. This article emphasizes on a normative juridical research with a statutory approach, empirical approach, and case study approach to comprehend electronic agreements and the law that regulates it as norms implemented in society. The type of data analyzed in this article are primarily secondary data from books, previous studies, journals related to electronic agreements, and Indonesian laws concerning electronic agreements. Previous survey found that more than 660 thousand electronic agreements were signed in early 2018, which is 159 percent higher than the previous period, indicating that the use of electronic agreements continue to increase and expand to various sectors in Indonesia. Therefore, the Indonesian law system must have an explanatory approach regarding this phenomena of technological advancement, specifically about electronic agreements. Several regulations researched and analyzed in this research disclose the importance of law related to electronic agreements, one of which is providing legal protection for the interests of the parties in electronic agreements. Supported by the legal perspective of “Law as A Tool Of Social Engineering” coined by Roscoe Pound, the existence of laws or regulations, in this case specifically regarding electronic agreements, functions as a law that can maintain the stability and balance of conflicting interests in society. Furthermore, the legal perspective of “Law as A Tool Of Social Engineering” sees the laws related to electronic agreements direct human attitudes to react to changes in society, in this case related to the technological advances that offers electronic agreements, so that people understand that agreements signed electronically have the same validity and binding force as conventional agreements signed physically. Keywords: electronic agreement; law as a tool of social engineering; Roscoe Pound.